Acetylation of woody lignocellulose: significance and regulation - Pawar, Prashant M.; Koutaniemi, Sanna; Tenkanen, Maija; Mellerowicz, Ewa J. (Frontiers in Plant Science, 2013)
Non-cellulosic cell wall polysaccharides constitute approximately one quarter of usable biomass for human exploitation. In contrast to cellulose, these components are usually substituted by O-acetyl groups, which affect their properties and interactions with other polymers, thus affecting their solubility and extractability. However, details of these interactions are still largely obscure. Moreover, polysaccharide hydrolysis to constituent monosaccharides is hampered by the presence of O-acetyl groups, necessitating either enzymatic (esterase) or chemical de-acetylation, increasing the costs and chemical consumption. Reduction of polysaccharide acetyl content in planta is a way to modify lignocellulose toward improved saccharification. In this review we: (1) summarize literature on lignocellulose acetylation in different tree species, (2) present data and current hypotheses concerning the role of O-acetylation in determining woody lignocellulose properties, (3) describe plant proteins involved in lignocellulose O-acetylation, (4) give examples of microbial enzymes capable to de-acetylate lignocellulose, and (5) discuss prospects for exploiting these enzymes in planta to modify xylan acetylation.